Impact of HOTAIR Gene Polymorphism and Environmental Risk on Oral Cancer. (June 2018) - Su, S.C.; Hsieh, M.J.; Lin, C.W.; Chuang, C.Y.; Liu, Y.F.; Yeh, C.M.; Yang, S.F.
Genetic and acquired factors are thought to be interrelated and imperative to estimate the risk and prognosis of oral squamous cell carcinoma (OSCC). HOX transcript antisense intergenic RNA ( HOTAIR ) plays crucial roles in gene regulation and is regulated in a variety of cancers. Polymorphisms in HOTAIR have been recently linked to the predisposition to diverse malignancies. In the present study, we aimed to evaluate the influences of HOTAIR gene polymorphisms, combined with environmental triggers, on the susceptibility to oral tumorigenesis. Four single-nucleotide polymorphisms of the HOTAIR gene— rs920778, rs1899663, rs4759314, and rs12427129—were tested in 1, 200 control participants and 907 patients with OSCC. We detected a significant association of rs1899663 with the risk of OSCC (adjusted odds ratio, 2.227; 95% confidence interval [95% CI], 1.197 to 4.146; P = 0.012) after adjustment for 3 potential confounders: smoking, betel quid chewing, and alcohol consumption. In further analyses where habitual exposure to each of 3 environmental factors was excluded, we found that, in addition to rs1899663, non–betel quid users who carried the polymorphic allele of rs920778 were more prone to develop OSCC than were those homozygous for wild-type allele (TC: odds ratio [OR], 1.472; 95% CI, 1.069 to 2.029; P = 0.018; TC+CC: OR, 1.448; 95% CI, 1.060 to 1.977; P = 0.020). Moreover, in exploring the relationship between HOTAIR gene polymorphisms and the clinical status of only patients with OSCC who were non–betel quid chewers (excluding the advanced clinical stage), we found that rs920778 and rs4759314 were correlated with the development of large-size tumors (OR, 1.891; 95% CI, 1.027 to 3.484; P = 0.04) and increased lymph node metastasis (OR, 4.140; 95% CI, 1.785 to 9.602; P = 0.001), respectively. Further functional assessments link rs920778 to the regulation of HOTAIR expression and epigenetic status. Our results reveal an interactive effect of HOTAIR gene polymorphisms and betel quid chewing on the development and progression of oral cancer.